Association Between Prostate Cancer Detection Rate and Year of Prostate Biopsy - Young Jun Uhm; Woojin Bang; Jae Hoon Chung; Cheol Young Oh; Hwanik Kim; Jin Seon Cho (Life)
As the prostate cancer (PCa) detection rate in South Korea is increasing year by year, authors investigated whether there was a plausible relationship between the year the prostate biopsy (PBx) was performed and the PCa detection rate. The medical records of 1628 patients who underwent PBx between 2008 and 2022, for each even-numbered year, were retrospectively reviewed. The primary outcome was the PCa detection rate, and the secondary outcome was to determine whether the PCa detection rate was significantly associated with the year of PBx and other clinical factors. When comparing baseline clinical factors among PBx patients by year, there were significant differences in age at the time of PBx (p = 0.017) and the number of PBx cores (p < 0.001). PCa detection rates ranged from 24.8% to 48.9% and were significantly positively correlated with the year of PBx (R2 = 0.885, p < 0.001). Subgroup analysis according to the prostate-specific antigen (PSA) level (≤10, over 10 to 20, >20 ng/mL) showed detection rates of 13.5–40.9%, 29.2–62.2%, and 73.3–92.6%, respectively (p < 0.001–0.021). Subgroup analysis according to the International Society of Urological Pathology grade group (ISUP GG) (1, 2–3, 4–5) showed that the PCa detection rate increased significantly over time in two subgroups (2–3: 4.8→16.7%, 4–5: 10.4→18.9%, all p = 0.002) except in the ISUP GG 1 subgroup. The PCa detection rate tends to increase with each successive biennial year of PBx. This increasing trend seems to be particularly pronounced in patients with relatively older age, higher PSA, and higher ISUP GG.